Peran Perserikatan Bangsa-Bangsa Dalam Menangani Kasus Pembunuhan Terhadap Demonstran Pada Konflik Internal Negara Menurut Statuta Roma Tahun 1998 di Myanmar - Putri, Haldina; HZ, Evi Deliana; Diana, Ledy (Peneliti.net, 2025)
Cases of human rights violations in the state's internal conflict occurred in Myanmar, where the Myanmar military took over the Myanmar government again. The coup, which began on February 1, 2021, was the beginning of the military's return to power in Myanmar. In the past, the coup was carried out on the grounds that the government in power at that time was unable to maintain the integrity of the country because there were many problems such as ethnic conflicts and failure to maintain economic stability. The UN should have changed the existing situation and in a state of many human rights violations that occurred, could carry out Humanitarian intervention or humanitarian intervention. Based on this presentation, two main problems arise that need to be examined, first related to how the role of the United Nations in handling cases of human rights violations in internal state conflicts according to the 1998 Rome Statute. while the second is how the form of intervention carried out by the United Nations in an effort to deal with cases of killings of protesters in the internal state conflict in Myanmar. This study uses a typology of normative legal research, which more specifically examines legal principles. In this study the author uses the nature of descriptive research, because the author describes the role of the United Nations in handling cases of demonstrator killings in Myanmar based on the 1998 Rome Statute. The result of the research conducted by the author is, The role of the UN is through the UN Charter, through various international agreements under the auspices of the UN, through its Security Council both by providing Security Council resolutions to the country, sending peacekeepers, using defense tools both land, sea, and air in protecting civilians, and intervening directly with regional organizations in those conflict areas. Furthermore, the form of intervention carried out by the United Nations (UN) in an effort to deal with cases of killing demonstrators in the internal state conflict in Myanmar is to issue Security Council Resolution Number 2669 of 2022 which asks Myanmar to immediately stop its actions. The resolution also asked ASEAN to help resolve internal conflicts in Myanmar. As for the International Criminal Court (ICC), Myanmar cannot be dragged to the ICC because Myanmar is not a country that ratified the 1998 Rome Statute.